Beef Cattle Breeder Income Improvement Strategy with Different Maintenance System in Langkat Regency - Sonya Elisabeth Silaen; Sri Fajar Ayu; Nevy Diana Hanafi (RIRAI Publisher, 2022)
This study aims to determine the strategy for developing beef cattle business after looking at the weaknesses, strengths, opportunities and threats that occur in Hinai District and Besitang District, Langkat Regency. This research was conducted in Hinai district and Besitang district, Langkat Regency in April-June 2022 with a total of 60 respondents. Analysis of the data used is using multiple linear analysis and the development strategy used is SWOT analysis. The results of the study note that the strategy obtained is the S-O Strategy, which is a strategy that uses internal strengths to take advantage of external opportunities, where internal strengths will take advantage of external events as follows: a. Utilization of good stables, human resources and experience of farmers to take advantage of the good natural and climatic conditions in Langkat to meet the high demand for buying cattle. b. Utilizing the experience of farmers and human resources in the use of AI technology, in meeting the high demand for cattle purchases.